ESTIMATION OF INFLUENCE CHANGE PARAMETERS ELLIPSOID ERRORS ON WITHSTAND LANDING TRAJECTORY - Казак, В.М.; Будзинська, Т.В.; Міщерякова, В.Ю. (Science-based technologies, 2009)
An analysis of RNP concept at the stage of an aircraft descent and landing was made. Control algorithm of an aircraft under the conditions of uncertainty, based on the tunnel concept of landing performance using an intel-ligent control system, based on the neural fuzzy-logic regulator, was presented.